Childhood Trauma in Women and Fragmented Interview Narratives – Some Interdisciplinary Methodological and Clinical Implications - Bifulco, Antonia (Lesya Ukrainka Volyn National University, 2021)
Trauma experience is understood through its expression in language, with implications for psycholinguistic and clinical research and analysis. Clinical research approaches often approach childhood trauma through investigative, semi-structured, retrospective interviews (e.g. Childhood Experience of Care and Abuse, CECA). This facilitates the narration of abuse history for systematic analysis in relation to clinical disorder. Interview techniques assist such history-telling, for example by ‘scaffolding’ the account, aiding memory through chronological questioning, using a factual focus and using probing questions to collect detail and resolve inconsistencies. However, some personal narratives are fragmented, incomplete, contradictory or highly emotional/dissociated from emotion. This can be explained by trauma impacts such as being emotionally frozen (forgetting and avoidance) or overwhelmed (emotional over-remembering) and is termed ‘unresolved trauma’ with links to attachment vulnerability. These narratives can make investigative interview research more challenging but can offer opportunities for secondary psycholinguistic analysis. Illustrative interview quotes from CECA childhood physical and sexual abuse narratives of three women are provided with comment on style of reporting. The women had recurrent trauma experience and later life depression and anxiety. The interview responses are examined in terms of seven characteristics taken from available literature (e.g. incoherent, contradictory, lack recall, time lapses, emotionality, blame and vividness). The concept of unresolved loss is discussed and whether the linguistic characteristics are specific to a trauma or to an individual. Factual investigative interviews and psycholinguistic analysis of narrative may find ways of combining for greater depth of understanding of unresolved trauma, to extend available methods and aid therapy.
Keywords: CECA interviews; childhood abuse; attachment; unresolved trauma; methods; attachment style